(untitled) (Fiep Bulletin - online, 2011)
This paper aims at presenting the motor profile of students participating in Piracema´s Project - "Swimming For People with special needs" , extension project of the University of Santa Cruz do Sul - UNISC / APAE.during 25 years, attending students with different pathologies. The project goal is to promote activities in the aquatic environment so that students increase their repertoire of attitudes in the water and when possible outside it. This study aims to evaluate the motor profile of the Piracema´s project participants. Participants were 6 students with mental disabilities, of both sexes, aged between 15 and 19 years. Were tested on the Motor Development scale(EDM), which include the following: small and Global Motion, Balance, Body Schema / Speed, Space Organization and language / Temporal Organization. The results obtained revealed that, in small motricity the students showed deficit, in the global motricity were showed satisfactory results and less, but the balance was presented a higher deficit among all aspects. Physical Scheme / Fast showed results between reasonable and unsatisfactory, Spacial Organization has obtained good results and lower and the last one evaluated Language / Temporal Organization results showed ups and downs. Thus, according to this study, where the practitioners were evaluated individually, so one can trace an individualized approach.